Online time, experience of cyber bullying and practices to cope with it among high school students in Hanoi. Issue 1 (June 2020) - Chi, Pham Thi Lan; Lan, Vu Thi Hoang; Ngan, Nguyen Hanh; Linh, Nguyen Thuy
This study is conducted to learn about experiences and practices to cope with cyberbullying among high school students in Hanoi and to explore the association between the average time of Internet used per day among high school students in Hanoi, Vietnam, and the risk of being cyberbullied. A total of 215 students aged 13–18 years completed an online survey using respondent-driven sampling method. The experience of being cyberbullied was examined using the modified Patchin and Hinduja's scale. The prevalence of experiencing at least one type of cyberbullying was 45.1%. The most common type of cyberbullying was being called by names/made fun of. The average daily time spent on Internet showed dose-response association with the risk of being cyberbullied. The prevalence of having experienced cyberbullying was 54% among subjects who used Internet >3 hours/day compared to 39% among those who used 1–3 hours and 30% among those who used <1 hour. In terms of practices to cope with this, most students chose to ignore it and not share information with their family or teacher. The most frequent method to overcome this problem was talking with friends (60.8%). Research shows that the prevalence of cyberbullying victimization in Hanoi was high, and student's practices to cope with this new form of bullying were not efficient. Online time had dose-response association with risk of cyberbullying. More attention is needed to increase level of society/school awareness to prevent cyberbullying in Hanoi.